(untitled) (Global Journal of Management and Business Research, 2021)
The objectif of this article is to analyse the contribution of tourism to job creation in the Cameroonian economy. To achieve this, we used the hypothetico-deductive method which consisted of browsing the literature and research works carried out on the problem of job creation by the tourism sector in Cameroun. These various studies have shown that tourism in Cameroun has contributed to job creation despite economic and security obstacles. The outlook for the sector shows an evolution in job creation if investments are made in particular in hotel infrastructure and parks.